Acellular dermal matrix based nipple reconstruction: A modified technique. (September 2017) - Vidya, Raghavan; Salem, Fathi; Iqbal, Fahad Mujtaba; Sircar, Tapan
Abstract: Nipple areolar reconstruction (NAR) has evolved with the advancement in breast reconstruction and can improve self-esteem and, consequently, patient satisfaction. Although a variety of reconstruction techniques have been described in the literature varying from nipple sharing, local flaps to alloplastic and allograft augmentation, over time, loss of nipple projection remains a major problem. Acellular dermal matrices (ADM) have revolutionised breast reconstruction more recently. We discuss the use of ADM to act as a base plate and strut to give support to the base and offer nipple bulk and projection in a primary procedure of NAR with a local clover shaped dermal flap in 5 breasts (4 patients). We used 5-point Likert scales (1 = highly unsatisfied, 5 = highly satisfied) to assess patient satisfaction. Median age was 46 years (range: 38–55 years). Nipple projection of 8 mm, 7 mm, and 7 mms were achieved in the unilateral cases and 6 mm in the bilateral case over a median 18 month period. All patients reported at least a 4 on the Likert scale. We had no post-operative complications. It seems that nipple areolar reconstruction [NAR] using ADM can achieve nipple projection which is considered aesthetically pleasing for patients.